Effect of miR-146a polymorphism on lipoic acid therapy in patients with T2DM peripheral polyneuropthy: Effect of miR-146a polymorphism on lipoic acid therapy - Li, Yan; Jia, Yukun (Cellular and Molecular Biology, 2023)
For investigating the impact of miR-146a rs2910164 polymorphism on the therapeutic efficacy of lipoic acid therapy in patients with type 2 diabetes mellitus (T2DM) peripheral neuropathy (DPN). 106 T2DM-DPN patients in our hospital from Jan. 2020- 2022 were selected. The probe detection method was utilized to determine the polymorphism of the miR-146a rs2910164 gene in peripheral blood. All patients were treated with zinc sulfate for 3 weeks period. According to the treatment effect, 37 patients who were ineffective in treatment will be divided into an ineffective group, and 79 patients who were effective in treatment will be divided into an effective group. The condition of miR-146a gene peptides was analyzed after treatment in both groups. The motor nerve conduction velocity (MNCV), sensory nerve conduction velocity (SNCV), and Toronto Clinical Scoring System (TCSS) scores of the median nerve and common peroneal nerve with different genotypes were compared between the 2 sets. The genotype frequencies of alleles G, GG, and GC in the valid group were lower than those in the invalid group; After treatment, MNCV and SNCV of CC genotype median nerve and common peroneal nerve in DPN patients were higher than those before treatment; The TCSS scores of the three genotypes less than post-treatment. The above results showed statistically significant differences (P<0.05). Lipoic acid is influenced by the miR-146a polymorphism gene in the treatment of T2DM-DPN patients, with the CC genotype having a lower susceptibility and the best clinical treatment effect.